Postracial Society as Social Fantasy: Black Communities Trapped Between Racism and a Struggle for Political Recognition. Issue 4 (12th May 2017) - Zevnik, Andreja
Abstract : The article discusses postracial society as social fantasy. It opens with a discussion of the lived experience of Americans and their attitude towards racism and social and political inequality. Drawing on the studies of public attitude, the article points towards a persisting racism the postracial society aimed to overcome and to the effect recent Black activism had on dismantling the fantasy. The article shows how on the one hand, racism is grounded in the unconscious and in the way a subject becomes politicized, while on the other hand, racism already permeates political categories such as rights or citizenship, concluding that a Black subject cannot exist politically as a Black subject. There is always something that a Black subject has in the excess and that mis‐fits with White political categories. The article turns to Lacan's psychoanalysis and his ideas of identification to address the relationship between the subject and the form of authority. Further, the article draws on the postcolonial psychoanalytically inspired ideas of Franz Fanon and W. E. B. Du Bois to frame the relationship between the White master and the Black subject and to present the impossibility the Black subject faces when met with the implicitly racially biased White political categories.